Changing Paradigms in the Management of Breast Cancer (Springer International Publishing, 2018)
This text is designed to present a comprehensive and state-of the-art approach to the management of breast cancer within the fields of surgery, medical oncology, and radiation oncology. Sections address changes in these fields. These areas include breast imaging, management of the axilla, atypical breast lesions, surgical margins, new techniques in breast reconstruction, and nipple sparing and contralateral mastectomies. Subsequent chapters focus on issues in medical oncology including, triple negative breast cancer and metastatic breast disease. New paradigms in radiation oncology are examined. Breast cancer treatment in the elderly and in young women, and genetic risk in breast cancer management is also be discussed. Written by experts in their field, each of these sections addresses advances and changes in the field. A brief review of the existing literature addressing the particular topic follows in each section. The text concludes with chapters on pathological issues and advances in radiation oncology. As access to a comprehensive multidisciplinary resource such as this is currently limited in the literature, Changing Paradigms in the Management of Breast Cancer represents the first single source to provide information on advances and outcomes for the physician caring for breast cancer patients in a multidisciplinary setting. .